Analysis of sequence variability and expression pattern of lactoferrin gene in Sahiwal cows (Bos indicus) and Murrah buffaloes (Bubalus bubalis) - Ankita Sharma,; S K Swami,; Manoj Kumar,; Monika Sodhi,; R S Kataria,; Pranay Jain,; Avnish Kumar Bhatia,; A K Mohanty,; S K Niranjan,; U K Shandilya,; Parvesh Kumari,; Manishi Mukesh, (Journal of Livestock Biodiversity, 2025)
Lactoferrin (LF), a bioactive glycoprotein is member of transferrin family and plays an important role in immune defense, iron homeostasis, antioxidant and regulation of cell growth. The present investigation was undertaken to analyze the sequence variations and expression pattern of LF gene between cattle and buﬀaloes. Blood was collected from Sahiwal cows (SAC), Karan Fries cows (KFC) and Murrah Buﬀaloes (MUB) to isolate peripheral blood mononuclear cells (PBMCs). Total RNA was extracted from PBMCs to synthesize cDNA. Sequence analysis has shown an ORF of 2127 bp with 780 amino acids in all cattle types and buﬀaloes. The analysis revealed no diﬀerence between LF cDNA sequences of SAC and KFC. Whereas, on comparing with exotic cattle, a total of 6 amino acid changes viz., I145V, S538T, T546N, T596S, K627E, and H632R were identified. The comparison between SAC and MUB revealed a total of 22 amino acid changes. The comparison of MUB LF cDNA sequences revealed homology of 96.23%, 96.75%, 91.67%, 91.95%, 73.16%, 70.20%, 64.21%, 73.83% with Indian native cattle, cross bred cattle, taurine cattle, sheep, goat, horse, human, mouse and pig respectively. Additionally, expression pattern of LF mRNA  in  somatic  cells  from  diﬀerent  lactation  stages  (colostrum  early,  mid  and  late  lactation)  of  SAC  and  MUB  was successfully evaluated. The analysis revealed highest transcript abundance of LF mRNA in colostrum samples indicating its role in enhancing immune system of new born calves. The study has led to sequence characterization LF cDNA in native, cross bred  and  riverine  buﬀaloes  and  identified  several  variations  that  could  prove  important  resource  for  future genotype: phenotype association studies. Further, the expression data has indicated that milk derived somatic cells could be utilized as valuable source to understand mammary gland functioning of Indian cows and buﬀaloes.